Urbanismo, crisis y austeridad - Álvaro Sevilla-Buitrago (Ciudades, 2015)
The current recession provides an opportunity to explore the interrelation of economic crunches and the production of space. This article outlines an interpretive framework to probe the fundamental role of urban and territorial restructuring in the formation, management and resolution of capitalist crises and, conversely, to understand periods of crisis as key stages in the history of urbanization and the development of planning techniques. I begin with a cursory review of several historical episodes of crisis, showing the strategic role played by the transformation of the built environment in these periods. After a brief analysis of the causes of the real estate bubble and subsequent bust in Spain, I suggest that the emerging “austerity urbanism” will deepen the agenda of neoliberal planning in recent decades. The article studies the main features of the forthcoming cycle of urban creative destruction and concludes with a series of critical proposals that could contribute to developing an alternative urbanism based on the tenets of sociospatial justice and democracy.